KAJIAN PEMASARAN AGROINDUSTRI SALE PISANG GORENG PADA PD BARKAH KERSANAGARA TASIKMALAYA - Cecep Pardani (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2021)
This study aims to determine: (1) the marketing channels of fried banana sale at PD Barkkah, (2) the cost, margin and profit of marketing fried banana sale at PD Barkkah, (3) the share of the price received by entrepreneurs (share) of fried banana sale. of the retail price on PD Barkkah. The type of research used is a case study method by taking the research location at PD Barkkah in Kersanagara Village, Cibeureum District, Tasikmalaya City. The sampling technique was carried out by purposive sampling method on the owner of the company named Mrs. Lilih Sholehah. The sample of marketing institutions was taken by snowball sampling of 2 wholesalers and 7 retailers. The results showed that: (1) There are two marketing channels for selling fried bananas at PD Barkkah, (2) Marketing channel 1 does not involve marketing agencies so that there are no marketing costs, the amount of marketing margins and profits. Marketing channel 2 involves two marketing institutions, namely wholesalers and retailers. Wholesalers spend marketing costs of Rp. 353.57 per kilogram, while retailers spend Rp. 315.17 per kilogram. The marketing margin at wholesalers is Rp. 2,000.00 per kilogram so that the marketing profit is Rp. 1,646.43 per kilogram. The marketing margin at retailers on channel 2 is Rp. 3,000.00 per kilogram so that the marketing profit is Rp. 2,684.83 per kilogram, and (3) The share price received by producers (Share) in channel 1 is 100%, and the share price received by producers (Share) in channel 2 is 86%.